El e-commerce y su influencia en el desarrollo económico del sector comercial Quevedo, año 2024 - Holguín Pisco, Silvia María (2025)
Electronic commerce (e-commerce) has become a key tool for the digital transformation of businesses. This phenomenon has revolutionized the way businesses interact with consumers and has generated significant impacts on the local economy. This study analyzes the impact of e-commerce on the economic development of the commercial sector in Quevedo, Ecuador, during the year 2024. Factors such as the growth of online sales, the digitalization of businesses, and changes in consumer behavior are examined. Using a quantitative and qualitative approach, data is collected through surveys and interviews with local merchants, which are subsequently tabulated using a data processing tool to prepare statistical tables and graphs that facilitate the presentation and interpretation of the results. The results identify the benefits and challenges of e-commerce, as well as its contribution to the city's economic growth. The research also proposes strategies to strengthen the adoption of e-commerce, improving the competitiveness and sustainability of the commercial sector. The budget to execute the project amounts to a total value of $495.00.